The performance and prospects of European Venture Capital - Roger Kelly (European Investment Fund (EIF), 2011)
This paper takes a critical look at possible explanations for poor European venture capital performance over the past two decades. Various supply-side hypotheses are discussed, including arguments relating to insufficient investment, investment in the wrong markets, exit difficulties due to fragmented exit markets, and fundraising difficulties arising due to differing regulatory regimes. In addition, a number of demand side issues, which have been used to suggest that Europe has a weaker entrepreneurial culture than the US, are scrutinized. The paper concludes that a number of these factors are likely to be responsible for the poor performance, and these factors can be summarised by the argument that within Europe, venture capital has not reached a critical mass, which is required for the industry to be self-sustaining and experience healthy returns. However, there is something of a catch-22 situation in this regard, as in order to achieve critical mass the industry needs to be positioned within an enabling venture capital ecosystem, which needs to evolve over time. On this basis, government interventions alone can only be of limited use in developing the venture capital industry. That said, there are some signs of venture capital ecosystems emerging in certain European regions.
Keywords: 330